The effective use of video in social media as persuasive technology for charity - Abdul Rahman, Maryam; Mahmud, Murni (IIUM Press, International Islamic University Malaysia, 2017)
This experimental study investigates the effective use of video in social media as persuasive technology to persuade teenagers towards charity. The study seeks to find the elements of a video that can be substantial to make a video attractive as well as having the ability to change the mindset of teenagers to charity. This research also unveils the relation of trigger between video elements in correlation with the emotions, charity act and social media. Three videos are selected from 10 pre-listed video; chosen, analyzed and filtered in a workshop. After three videos were selected, 49 students participated in the survey while 18 students participated in the interview session to ascertain the element of a video that has the ability to persuade teenagers towards charity. The outcome of this study recommend the element of storyboard as the most persuasive element that can give the impact to a video. The study conclude that the video designed should have the important element of realism with the right choice of images, the right sound effect that play role of attraction and most importantly arranged well in plots of storyboard that makes it the very best effective and persuasive video. The element of realism, images, explosion sound effect and storyline is the most leading elements of a video to attract teenagers. The outcome of the study conclude that the element of realism, images and explosion is dominant but the element of storyboard is the strongest and most dominant element to make a persuasive video. Without a good storyboard it will not be as appealing or persuasive to the teenage viewer. Videography techniques or themes only adds in as secondary factor of persuasion.